An Assessment of Community and Extension Service: Basis for Continual Improvement - Seranno, Ma. Gertrudes S; Barros, Divina D; Sabalza, Rechelle B; Reyes-Chua, Ethel; Hernandez, Alma R; Soliman, Remon T (ASEAN Multidisciplinary Research Journal, 2022)
Community programs are about developing partnerships, relationships and connections with the community. One of the fundamental principles of an organization is to serve its community, the educators from various institutions were gathered and came up with community and extension programs in the community/schools. This research aimed to assess the Bayanihan sa Paaralan for Brigada Eskwela 2021 as Community and Extension Service rendered by Cavite Oakwood Good Samaritan 102 Lions Club as basis for continual improvement. Using the descriptive-qualitative methods of research, the level of satisfaction of the members of the community were determined, the strategies of the implementers in the conduct of the community and extension programs were discussed, the problems encountered, and the community’s feedback towards the programs and activities were explored. A researcher-made survey questionnaire was utilized and this was conducted to 40 respondents. On the other hand, there were some difficulties faced by the implementers during the actual execution of these programs. Using the Kolb’s Experiential Learning Cycle, the researchers were inspired to create a collection of themes that would serve as a roadmap for continuous development. As a consequence, good feedback from the community was disclosed, and they requested that these community and extension programs and activities, particularly in the areas of education, health, livelihood, environment, and socio-economic development to be continued and perpetuated. Finally, each program should be evaluated on a regular basis to identify its strengths and limits, as well as to address any problems that arise both before and after its implementation.